Canakinumab in adults with steroid‐refractory pyoderma gangrenosum. (1st November 2015) - Kolios, A.G.A.; Maul, J.‐T.; Meier, B.; Kerl, K.; Traidl‐Hoffmann, C.; Hertl, M.; Zillikens, D.; Röcken, M.; Ring, J.; Facchiano, A.; Mondino, C.; Yawalkar, N.; et al.
Summary: Background: Pyoderma gangrenosum (PG) is a rare, neutrophilic, ulcerative skin disease that is difficult to treat, especially when unresponsive to steroids. Objectives: To determine whether canakinumab is an effective and safe treatment in PG. Methods: Five adult patients with clinically and histologically confirmed steroid‐refractory PG were enrolled in this prospective open‐label study. They received canakinumab 150 mg subcutaneously at week 0 with an optional 150 mg at week 2 in case of an inadequate response [Physician's Global Assessment (PGA) ≥ 2], and an optional 150–300 mg at week 8 depending on PGA. The primary clinical end point was clinical improvement (PGA at least −1 from baseline) and/or complete remission (PGA 0 or 1) at week 16. Real‐time quantitative polymerase chain reaction was performed on skin samples to quantify cytokine mRNA levels. Results: Interleukin (IL)‐1β and its known target genes IL6, CXCL8 and IL36A were significantly increased in lesional skin of PG. Under canakinumab therapy, four of five patients showed a decrease in target‐lesion size, PGA and Dermatology Life Quality Index (DLQI), and three of five achieved complete remission. The mean diameter of target lesions decreased from 4·32 ± 2·6 cm at visit 1 to 0·78 ± 1·3 cm at visit 7 ( P = 0·03). Mean DLQI decreased from 15 ± 5 at visit 1 to 8 ± 4 by visit 7 ( P = 0·01). Adverse effects were reported in two patients: fatigue in one and worsening of disease at a nontarget lesion in the other. Conclusions: Our data indicate that IL‐1β plays a key pathogenic role in PG and canakinumab may represent a therapeutic option for steroid‐refractory PG.